Alfred Marshall e a institucionalização da escola de economia - Pavon, Paula Regina (2006)
So far, Alfred Marshall s work (1842-1924) has been little explored in Brazil. Typically, Marshall is mentioned in economic historiography only as the author of the so-called marginalist or neoclassic school. Since our aim in this paper is to give a broader visibility to this author, it appeared to us that the initial steps here should not be centered around the complex discussion that involves economic theories or the mathematical aspects of such discussions. As regards the latter, Marshall himself insisted in distributing them into appendices aimed at, as told by the author, rendering his work accessible to as many people as possible. Therefore, we decided to follow this author s intellectual path in order to out the contributions he gave to the definition of economic science from his major book, Principles of Economics, published in 1890. Marshall became the responsible for the institutionalization of a new science when he founded the School of Economics and Politics at Cambridge University, defining the role of both economics and economists. The scope of this research encompasses two principal lines: first, to approach Marshall s work from the conditions found in the Victorian age, between 1837 and 1901. In this sense, we looked for those elements which influenced the formation of the author, and which have been influenced by him. Then, we looked for the philosophic and scientific aspects of Marshall s ideas contained in his book Principles of Economics, in which he defines the extent of economic studies.